2022
DOI: 10.1002/ardp.202200033
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and biological evaluation of isatin‐indole‐3‐carboxaldehyde hybrids as a new class of xanthine oxidase inhibitors

Abstract: A novel series of triazole-linked isatin-indole-3-carboxaldehyde hybrids based on the febuxostat skeleton and its binding site interactions were rationally designed and synthesized as potential xanthine oxidase inhibitors. Among the synthesized hybrids, A19 showed the most potent xanthine oxidase inhibition (IC 50 = 0.37 µM) with the mixed-type inhibitory scenario. Structure-activity relationship studies revealed that methoxy (OCH 3 ) substitution on position 5 of the isatin nucleus and a two-carbon distance b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 44 publications
(60 reference statements)
0
11
0
Order By: Relevance
“…Our study indicated that microplastics stimulate the GST activity as the exposure period increased. LDPE had a significant effect on GST activity after 7 days of exposure Molecular docking studies is an effective tool to analyze the possible binding sites of a ligand in a particular enzyme and its interactions with the catalytic or non-catalytic sites at a molecular level that are responsible for the modulation of the activity of that enzyme (Chowdhary et al, 2022;Singh et al, 2022;Yuvaraj et al, 2021). Superoxide dismutase (SOD) catalyzes the conversion of superoxide radicals to oxygen and hydrogen peroxide resulting in the protection of cells from oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Our study indicated that microplastics stimulate the GST activity as the exposure period increased. LDPE had a significant effect on GST activity after 7 days of exposure Molecular docking studies is an effective tool to analyze the possible binding sites of a ligand in a particular enzyme and its interactions with the catalytic or non-catalytic sites at a molecular level that are responsible for the modulation of the activity of that enzyme (Chowdhary et al, 2022;Singh et al, 2022;Yuvaraj et al, 2021). Superoxide dismutase (SOD) catalyzes the conversion of superoxide radicals to oxygen and hydrogen peroxide resulting in the protection of cells from oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Keeping in view the pharmacological profile of isatin [70,71] and 1,2,3-triazole nucleus, Dehwal et al designed and synthesised 5-Fluoro-1H-indole-2,3-dione-triazoles and evaluated for antifungal activity against the Candida albicans. Among them, compound 42 was found to be most potent antifungal agent against Candida albicans with MIC value of 0.0075 μmol/mL as compared with standard fluconazole (MIC value of 0.0051 μmol/mL).…”
Section: 23-triazole Derivatives Containing Isatin Moietymentioning
confidence: 99%
“…Keeping in view the pharmacological profile of isatin [70,71] and 1,2,3‐triazole nucleus, Dehwal et al . designed and synthesised 5‐Fluoro‐1H‐indole‐2,3‐dione‐triazoles and evaluated for antifungal activity against the Candida albicans .…”
Section: 23‐triazole Derivatives With Antifungal Activity Against As ...mentioning
confidence: 99%
“…Additionally, the antiproliferative activity was attenuated by lengthening the carbon spacer between morpholine and isatin. [ 99 ] Specifically, hybrids 59a,b (GI 50 : 4.36 and 9.22 µM) were comparable to plumbagin (GI 50 : 3.50 µM) and were more effective compared with tamoxefene (GI 50 : 50 µM). Mechanistically, hybrid 59a may result in G2/M‐phase mitotic arrest.…”
Section: Miscellaneous Indole/isatin Hybridsmentioning
confidence: 99%